PENGARUH KOMPETENSI, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. TRIJAYA PUTRA SEJAHTERA - Septian Dwi Cahyo; Nurleila Jum’ati (Jurnal Ekonomi, Bisnis dan Social, 2024)
This study aims to analyze the effect of competence, work environment and work discipline on the performance of employees of PT. Prosperous Trijaya Putra. The sample in this study is PT. Prosperous Trijaya Putra. The sampling technique in this study used a non-probability sampling technique, namely purposive sampling, with a total of 61 respondents. Statements are given using a questionnaire. Responses from respondents were analyzed using Statistical Product and Service Solutions (SPSS) version 21. This study uses multiple linear regression analysis. Hypothesis testing is done partially (t-test) and simultaneously (F-test). The results of this study indicate that competence, work environment and work discipline simultaneously have a positive and significant effect on employee performance. Partially, competence and work discipline affect employee performance. But the work environment has no effect on employee performance. The independent variable in this study has an influence of 44.7% on employee performance and the rest is influenced by other variables that are not in this study.